Water Vapor Vertical Profiles on Mars in Dust Storms Observed by TGO/NOMAD. Issue 12 (28th December 2019) - Aoki, S.; Vandaele, A. C.; Daerden, F.; Villanueva, G. L.; Liuzzi, G.; Thomas, I. R.; Erwin, J. T.; Trompet, L.; Robert, S.; Neary, L.; Viscardy, S.; Clancy, R. T.; et al.
Abstract: It has been suggested that dust storms efficiently transport water vapor from the near‐surface to the middle atmosphere on Mars. Knowledge of the water vapor vertical profile during dust storms is important to understand water escape. During Martian Year 34, two dust storms occurred on Mars: a global dust storm (June to mid‐September 2018) and a regional storm (January 2019). Here we present water vapor vertical profiles in the periods of the two dust storms ( Ls = 162–260° and Ls = 298–345°) from the solar occultation measurements by Nadir and Occultation for Mars Discovery (NOMAD) onboard ExoMars Trace Gas Orbiter (TGO). We show a significant increase of water vapor abundance in the middle atmosphere (40–100 km) during the global dust storm. The water enhancement rapidly occurs following the onset of the storm ( Ls ~190°) and has a peak at the most active period ( Ls ~200°). Water vapor reaches very high altitudes (up to 100 km) with a volume mixing ratio of ~50 ppm. The water vapor abundance in the middle atmosphere shows high values consistently at 60°S‐60°N at the growth phase of the dust storm ( Ls = 195°–220°), and peaks at latitudes greater than 60°S at the decay phase ( Ls = 220°–260°). This is explained by the seasonal change of meridional circulation: from equinoctial Hadley circulation (two cells) to the solstitial one (a single pole‐to‐pole cell). We also find a conspicuous increase of water vapor density in the middle atmosphere at the period of the regional dust storm ( Ls = 322–327°), in particular at latitudes greater than 60°S. Plain Language Summary: The most striking phenomenon on Mars is a planet‐encircling storm, "global dust storm." Once it starts, the floating dust covers the whole atmosphere for more than several weeks. Recent studies suggest that dust storms effectively transport water vapor from the near‐surface to the middle atmosphere. In June to September 2018 and January 2019, a strong global dust storm and a regional storm occurred on Mars, respectively. This study investigates altitude profiles of water vapor in the Mars atmosphere measured during the dust storms, by using brand‐new measurements by Nadir and Occultation for Mars Discovery onboard the ExoMars Trace Gas Orbiter. We confirm that the water vapor expanded into the middle atmosphere, and we find that the water vapor reached very high altitudes (up to 100 km) during the dust storms. The dust storms intensify the atmospheric dynamics and heat the atmosphere. As a result, water vapor is lifted to higher altitudes and distributes along the meridional circulation. Key Points: We present vertical profiles of water vapor in the Martian atmosphere during global and regional dust storms in 2018‐2019 We show a rapid and significant increase of water vapor in the middle atmosphere (40‐100 km) during both global and regional dust storms Water vapor reaches very high altitudes, at least around 100 km, during the global dust storm